Do Ads Influence Editors? Advertising and Bias in the Financial Media - Reuter, Jonathan; Zitzewitz, Eric (Quarterly Journal of Economics, 2006)
The independence of editorial content from advertisers' influence is a cornerstone of journalistic ethics. We test whether this independence is observed in practice. We find that mutual fund recommendations are correlated with past advertising in three personal finance publications but not in two national newspapers. Our tests control for numerous fund characteristics, total advertising expenditures, and past mentions. While positive mentions significantly increase fund inflows, they do not successfully predict returns. Future returns are similar for the funds we predict would have been mentioned in the absence of bias, suggesting that the cost of advertising bias to readers is small.